The expression of tgf-ï¢1 after low level laser therapy in inflammation animal model - Subadi, Imam; Wardhani, Indrayuni Lukitra; Andriati, Andriati (Folia Medica Indonesiana, 2017)
Pain is the most common complaints in everyday practice. Pain is a clinical manifestation caused by stimuli due to potential tissue damage. Low level laser therapy (LLLT) has been used in reducing pain. One of indicator tissue healing is activation of transforming growth factor -b1(TGF-b1). Tissue healing will eliminate the pain. Do LLLT stimulate TGF-b1 expression? The objective of this study was to investigate the expression of TGF-b1 in low level laser therapy. Thirty male Wistar rats, body weight 250 – 300 gram, 3 month old, were divided into 3 groups, negative control (n=10), positive control (n=10) and treatment groups (n=10). The positive control and treatment groups were injected with Complete's Freund Adjuvant (CFA) 100 mL at left footpad. The treatment group treated with low level laser therapy Lasermed type 2100 wavelength 905 nm, out power 25-500 mW, dose 1 joule/cm2;5 times with interval 24 hours on left footpad. Samples were taken from the skin of footpad and immunohistochemical examination with monoclonal antibody anti- TGF-b1. Calculations carried out on brown reaction in macrophage cell. Data were analyzed using the Games Howell with SPSS 17. There were significant differences in the expression of TGF-b1 in treatment group (15.8±3.1) compared with the positive control group (3.9±1.1) and negative control group (4.6±2.1). There were no significant differences between expression TGF-b1 in positive control group and negative control group. In conclusion, low level laser therapy increased the expression of TGF-b1.